The USP8 mutational status may predict long‐term remission in patients with Cushing's disease. (23rd July 2018) - Albani, Adriana; Pérez‐Rivas, Luis G.; Dimopoulou, Christina; Zopp, Stephanie; Colón‐Bolea, Paula; Roeber, Sigrun; Honegger, Jürgen; Flitsch, Jörg; Rachinger, Walter; Buchfelder, Michael; Stalla, Günter K.; Herms, Jochen; et al.
Summary: Objective: Almost half of the cases of Cushing's disease (CD) tumours carry recurrent activating somatic mutations in the ubiquitin‐specific protease eight gene ( USP8 ). The USP8 mutational status could predict remission in patients with CD, so our objective was to correlate the presence of somatic USP8 mutations with the rate of recurrence after transsphenoidal surgery (TSS) retrospectively. Design: Biochemical, radiological and clinical data were retrospectively assessed in 48 patients. USP8 mutational status was determined from corticotroph tumour samples. Association between USP8 mutational status, remission and recurrence was investigated. Patients: Patients with Cushing's disease from a single‐centre cohort who underwent TSS between 1991 and 2012. Measurements: Long‐term remission and recurrence rate after TSS with at least 6 months follow‐up. Biochemical, radiological and clinical data, including sex, age at diagnosis, tumour size and pre‐operative hormonal levels. USP8 mutational status. Results: Patients with USP8 mutant corticotroph tumours (18 of 48; 37%) were diagnosed significantly earlier (mean ± SD 46 ± 10 years vs 53 ± 11 years; P  =   0.028) and presented with higher pre‐operative 24‐hour urinary‐free cortisol levels (median IQR μg/24 hours 1174.0, 1184.5 vs 480.0, 405.3; P  =   0.045). The incidence of recurrence in a 10‐year follow‐up was significantly higher in patients with USP8 mutant tumours after the initial remission (58% vs 18% P  =   0.026). Recurrence appeared significantly earlier in these patients (months 70, 44‐97 95% CI vs 102, 86‐119 95% CI; P  =   0.019). Conclusion: Recurrence appears to be more frequent and earlier after TSS in patients with USP8 mutant corticotroph tumours.